If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -93 = 3x + 105 Reorder the terms: -93 + 12x = 3x + 105 Reorder the terms: -93 + 12x = 105 + 3x Solving -93 + 12x = 105 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -93 + 12x + -3x = 105 + 3x + -3x Combine like terms: 12x + -3x = 9x -93 + 9x = 105 + 3x + -3x Combine like terms: 3x + -3x = 0 -93 + 9x = 105 + 0 -93 + 9x = 105 Add '93' to each side of the equation. -93 + 93 + 9x = 105 + 93 Combine like terms: -93 + 93 = 0 0 + 9x = 105 + 93 9x = 105 + 93 Combine like terms: 105 + 93 = 198 9x = 198 Divide each side by '9'. x = 22 Simplifying x = 22
| (X^2)-((y^2)/35)=1 | | 0.33(x-16)=-2(x-3)+4 | | 2(3x-2)-2=2(x-2)+6 | | -8(3x+1)=8x-7(6x+5) | | -r-5(2r+2)=-76 | | 5/7x.25 | | X=3(6y-8) | | 2[2y+2]-5y=1 | | u-2=5 | | 90+x=5x | | n=30-25 | | 8t=3[t+55] | | -7x+3(3x+4)=-10 | | -7x+3(3x+4)=-10 | | (4x^2+12)-(10x^2-11)= | | y=400-.8 | | -7x+3(3x+4)=-10 | | 2+2=q | | 4-2x+2=-64 | | n=40-10 | | 2n^2-6=0 | | 4-2x=10+x | | 10-3b=-7b+6b | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 6+z(9)=9 | | 4y-a=5a+6(3-y) | | Ln40/ln4 | | 2-(1/3)t |